RASIO KEUANGAN : DETERMINAN PERTUMBUHAN LABA STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA (Jurnal Akuntansi, 2018)
This study aims to strengthen the influence of Financial Ratios to Earning Growth (BEI). The sample selection with purposive sampling were 61 companies which held the year 2012 - 2016 ie 5 years and only 21 samples taken with the number of observation 105, the selection based on annual audit report. The independent variables studied are financial ratios consisting of Current Ratio (CR),Debt to Asset Ratio (DAR), Total Asset Turnover (TAT) and Net Profit Margin (NPM), while the dependent variable is Earning Growth (EG). The results of this study show simultaneously current ratio, debt to ssset ratio, total asset turnover and net profit margin significant to earning growth at manufacturing companies in Indonesia Stock Exchange. Partially, only the current asset variable has not significant effect to earning growth. Ratio of debt to Assets ratio, total asset turnover and net profit margin have a significant influence to earning growth in Indonesia Stock Exchange.